The Effect of Sleep Habits on the Incidence of Anemia Among Adolescent Girls at SMKN 2 Majene - Rasmawati; Murdiana (Papua Medicine and Health Science, 2025)
Anemia is a condition characterized by a decrease in hemoglobin levels in the body. Hemoglobin is an iron-containing protein found in red blood cells that functions to transport oxygen from the lungs throughout the body. One of the factors that can influence hemoglobin levels is sleep habits. Sleep disturbances can lower sleep quality, which affects the process of cell regeneration, including hemoglobin production, thereby potentially triggering anemia. Sufficient and high-quality sleep is essential for the formation of new cells and the repair of damaged ones. This study aimed to determine the effect of sleep habits on the incidence of anemia among adolescent girls at SMKN 2 Majene. This research employed a quantitative design with a cross-sectional approach. The population consisted of all eleventh-grade adolescent girls at SMKN 2 Majene. A total of 42 respondents were selected using purposive sampling. Data were analyzed using the Chi-square test. The univariate analysis showed that 40 respondents (95.2%) had poor sleep habits. The bivariate analysis revealed a p-value of 0.042 (p < 0.05), indicating a significant effect of sleep habits on the incidence of anemia. These findings underscore the importance of maintaining good sleep habits to prevent anemia among adolescent girls.